Deep brain stimulation can suppress pathological synchronisation in parkinsonian patients. Issue 5 (9th October 2010) - Eusebio, A; Thevathasan, W; Doyle Gaynor, L; Pogosyan, A; Bye, E; Foltynie, T; Zrinzo, L; Ashkan, K; Aziz, T; Brown, P
Abstract : Background: Although deep brain stimulation (DBS) of the subthalamic nucleus (STN) is a highly effective therapeutic intervention in severe Parkinson's disease, its mechanism of action remains unclear. One possibility is that DBS suppresses local pathologically synchronised oscillatory activity. Methods: To explore this, the authors recorded from DBS electrodes implanted in the STN of 16 patients with Parkinson's disease during simultaneous stimulation (pulse width 60 μs; frequency 130 Hz) of the same target using a specially designed amplifier. The authors analysed data from 25 sides. Results: The authors found that DBS progressively suppressed peaks in local field potential activity at frequencies between 11 and 30 Hz as voltage was increased beyond a stimulation threshold of 1.5 V. Median peak power had fallen to 54% of baseline values by a stimulation intensity of 3.0 V. Conclusion: The findings suggest that DBS can suppress pathological 11–30 Hz activity in the vicinity of stimulation in patients with Parkinson's disease. This suppression occurs at stimulation voltages that are clinically effective.